2022
DOI: 10.1097/sla.0000000000005735
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Surgical Outcomes Linked to Co-occurring Smoking and Risky Alcohol Use Among General Surgery Patients

Abstract: Objective: To assess associations between co-occurring preoperative smoking and risky alcohol use on the likelihood of adverse surgical outcomes. Background: Risky alcohol use and smoking are the known surgical risk factors with a high co-occurrence and additive adverse effects on multiple organ systems that impact surgical health, yet no research has evaluated the impact of co-occurrence on surgical outcomes. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…This total prevalence of risky alcohol use identified using NLP (14.5%) aligns more with the expected prevalence of risky alcohol use and alcohol use disorders in the population and provides further support for the accuracy of NLP (Grant et al., 2017). The low rate of identification of alcohol problems using ICD codes alone is consistent with other studies in the literature (Fernandez et al., 2023; Fernandez, Bohnert, et al., 2022; Grant et al., 2017).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This total prevalence of risky alcohol use identified using NLP (14.5%) aligns more with the expected prevalence of risky alcohol use and alcohol use disorders in the population and provides further support for the accuracy of NLP (Grant et al., 2017). The low rate of identification of alcohol problems using ICD codes alone is consistent with other studies in the literature (Fernandez et al., 2023; Fernandez, Bohnert, et al., 2022; Grant et al., 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Studies on alcohol use among surgery patients that use EHR data, vastly under‐identify patients drinking at risky levels for surgery. For example, one recent study found only 2.8% of elective surgery patients were classified with risky drinking (>2 drinks/day) based on EHR review, suggesting automated chart review methods, such as the one presented herein, could improve patient identification (Fernandez, Bohnert, et al., 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Many for-profit entities, such as pharmaceutical companies, device companies, and the health insurance industry, greatly benefit from the work and the discovery of surgeon scientists. 19,20 Partnerships with these organizations can help bridge the funding gap and support innovative quality research or novel device and drug development. Institutions and departments should consider these potential partnerships and potentially build a revenue stream that could be directed toward funding relevant research efforts of young investigators.…”
Section: Societies and Funding Agenciesmentioning
confidence: 99%
“…Many for-profit entities, such as pharmaceutical companies, device companies, and the health insurance industry, greatly benefit from the work and the discovery of surgeon scientists 19,20 . Partnerships with these organizations can help bridge the funding gap and support innovative quality research or novel device and drug development.…”
Section: Societies and Funding Agenciesmentioning
confidence: 99%
“…Nonetheless, there exists compelling evidence that both alcohol usage and risky drinking behaviors are prevalent among individuals who have successfully recovered from cancer and those undergoing treatment [ 8 ]. It is crucial to emphasize that alcohol consumption is linked to heightened postoperative risks [ 9 , 10 ] and exacerbates the efficacy of cancer therapy [ 8 ]. These factors potentially carry implications for the outcomes of surgical interventions in patients afflicted with urological cancers.…”
Section: Introductionmentioning
confidence: 99%